Análise volumétrica de fissuras alveolares pré e pós-expansão ortodôntica da maxila - Lessa Filho, Luciano Schwartz (2015)
The rehabilitation of patients with lip and palate cleft can be more efficient when the volume of the alveolar cleft is obtained through Computered Tomography (CT) scans. Therefore, this work aimed to evaluate the volume of alveolar cleft in patients with unilateral lip and palate cleft before and after the orthodontic maxillary expansion by Cone-Beam Computed Tomography scans (CBCT). The study was conducted using the database of the Rehabilitation Center of Lip and Palate Cleft (CERLAP) at PUCRS Faculty of Dentistry. 26 patients were assessed during pre-expansion period (T1) and after the maxillary orthodontic expansion (T2) with two reviews (AV1 and AV2) in each period, performed by the same examiner. The software used for the measurement was the OsiriX MD. The average before and after the operation (T1 and T2) and the average of reviews (AV1 and AV2) were compared using the Student t test for paired samples at 5% of probability. To compare the volume between genders and age groups, we applied the Student t test for independent samples. We used the Bland-Altman method with limits of 95% in the evaluation of concordance between AV1 and AV2, which confirmed the high degree of reproducibility of the proposed method with 92% (24 of 26 measures) agreement between the measurements performed in the two periods. The Pearson correlation at T1 was r = 0.94 and r = 0.88 at T2. The average volume on AV1 and AV2 was 1.10 ± 0.48 and 0.98 ± 0.46 cm3, respectively, and both in the AV1 and AV2 it was observed that clefts on T2 had greater volume than the clefts on T1 (p = 000). The average on T1 and T2 were 0.86 ± 0.37 and 1.21 ± 0.57 cm3, respectively, with the difference being about 41% compared to T1. The volume of the alveolar cleft did not differ between genders, age groups and sides of the cleft. It was concluded that the software OsiriXMD has a high degree of reproducibility to delimit the alveolar cleft and measuring its volume with the use of CBCT image.